Pelatihan Pemanfaatan Lahan Pekarangan Secara Produktif dengan Penanaman Sayuran dan Tanaman Obat Keluarga di Kelurahan Pajalesang Kecamatan Lilirilau Kabupaten Soppeng - Pratiwi Mushar Mushar; Citra Maelani Firman (Jurnal Pengabdian Masyarakat Hasanuddin (JPMH), 2022)
Covid-19 has had an impact on various aspects of people's lives, including agriculture, which is related to people's consumption needs. Efforts to overcome this, one of which can be done by utilizing the yard. At present, the people of Pajalesang Village Lilirilau District Soppeng Regency are still not using their yards by planting productive plants such as vegetables and family medicinal plants, therefore it is important to carry out training activities on the use of yardland by planting vegetables and family medicinal plants as a pilot with the aim that the community can take advantage of the land that is used in the yard. exist in this pandemic era so that it can meet the family's nutrition and health needs. The method of service for this activity is conducting training by providing offline or face-to-face pilots with the community in the yard. This activity resulted in two productive yards. This activity can be said to run well as it should thank to the support of various parties.